2016
DOI: 10.1515/hmbci-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic memory in metabolism and cancer

Abstract: Hyperglycemia is a hallmark of both type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). Recent evidence strongly suggests that prolonged exposure to hyperglycemia can epigenetically modify gene expression profiles in human cells and that this effect is sustained even after hyperglycemic control is therapeutically achieved; this phenomenon is called hyperglycemic memory. This metabolic memory effect contributes substantially to the pathology of various diabetic complications, such as diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…These infants are susceptible to accelerated rates of cell growth from increased insulin‐like growth factor 1 overexpression as a consequence of poorly controlled maternal hyperglycaemia. Indeed, hyperglycaemia itself is now understood to epigenetically modify gene expression profiles in human cells and possibly increase cancer risk even after glycaemic control is regained .…”
Section: Discussionmentioning
confidence: 99%
“…These infants are susceptible to accelerated rates of cell growth from increased insulin‐like growth factor 1 overexpression as a consequence of poorly controlled maternal hyperglycaemia. Indeed, hyperglycaemia itself is now understood to epigenetically modify gene expression profiles in human cells and possibly increase cancer risk even after glycaemic control is regained .…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting views. Lee et al [60] reported that the risk of prostate cancer was reduced in patients with diabetes. Some metabolic and hormonal factors, including blood glucose and insulin, may involve.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies have been conducted to investigate DR in diabetic complications [ 5 ]. As a consequence, a special phenomenon hyperglycemic memory or metabolic memory has been discovered, which occurs when human cells have prolonged exposure to hyperglycemia conditions even after hyperglycemic control is therapeutically achieved [ 6 , 7 ]. As a result, disease may continue to occur or progress after the patient’s blood glucose has been controlled for a long period of time and cells may continue to be damaged after the high glucose environment has been removed [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%